Case report: Acute audiovestibular presentation following hemi-pontine infarction - Koohi, Nehzat; Haider, Salman; Kharytaniuk, Natallia; Werring, David J; Bamiou, Doris-Eva; Kaski, Diego (Frontiers in Stroke, 2023)
Posterior circulation stroke is an uncommon cause of sudden-onset sensorineural hearing loss (SSNHL). Anterior inferior cerebellar artery occlusion results in ipsilateral peripheral audiovestibular dysfunction. Few reports describe posterior circulation stroke presenting with contralateral SSNHL and acute vestibular and focal neurological signs. We present a case of contralateral SSNHL and isolated acute central vestibular dysfunction in the absence of other central focal neurological deficits. To the best of our knowledge, this has not been described to date. The patient was identified to have asymmetrical SSNHL, subtle skew deviation with left head tilt, and significant refixation saccades on video head impulse test despite bilaterally normal vestibulo-ocular reflex gains. Left pontine infarct was suspected and confirmed on magnetic resonance imaging. The patient was treated with an appropriate antiplatelet regimen. We highlight the importance of a thorough clinical diagnostic work-up as posterior circulation strokes with isolated audiovestibular deficits can be easily missed if other significant neurological deficits are absent.